2022
DOI: 10.1177/1532673x221109516
|View full text |Cite
|
Sign up to set email alerts
|

Incivility in Congressional Tweets

Abstract: Civility in political discourse is often thought to be necessary for deliberation and a healthy democracy. However, incivility is on the rise in political discourse in the United States—even from members of Congress—suggesting that political incivility may in fact be a tool to be used strategically. When and why, then, do members of Congress use incivility in their rhetoric? We develop and test expectations for the usage of political incivility by members of Congress on Twitter, using every tweet sent by a mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…This approach, centered around the fostering of political division, maps neatly onto the rhetorical approaches of political elites on social media and aligns with the definition of polarizing rhetoric utilized in previous academic research in this area (e.g. Ballard et al, 2022b; Russell, 2018). Importantly, this does not merely encompass discussion of divisive topics (which can very much still be done in a non-polarizing fashion) and this concept is also distinct from polarized rhetoric, which merely implies the presence of dichotomous rhetorical strategies used by different groups, but does not necessarily speak to the tone or manner in which this is done.…”
Section: Polarizing Rhetoricmentioning
confidence: 94%
See 2 more Smart Citations
“…This approach, centered around the fostering of political division, maps neatly onto the rhetorical approaches of political elites on social media and aligns with the definition of polarizing rhetoric utilized in previous academic research in this area (e.g. Ballard et al, 2022b; Russell, 2018). Importantly, this does not merely encompass discussion of divisive topics (which can very much still be done in a non-polarizing fashion) and this concept is also distinct from polarized rhetoric, which merely implies the presence of dichotomous rhetorical strategies used by different groups, but does not necessarily speak to the tone or manner in which this is done.…”
Section: Polarizing Rhetoricmentioning
confidence: 94%
“…These messages were then classified for polarizing rhetoric using a fine-tuned supervised machine learning process, based on an updating of an established tweet classifier from Ballard et al (2022b). Ballard et al’s original polarizing rhetoric classifier is specifically trained using a hand-coding of 5000 congressional tweets across the period 2007 to 2020, effectively training a classification model directly attuned to the rhetorical techniques of elected officials in the United States.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its launch in 2007, Twitter has become a popular and easy way for politicians to directly communicate with constituents (Munger et al, 2016). Research to this point has found that Twitter is used by political elites to express partisan and ideological positions, share relevant policy information (Ballard et al, 2022(Ballard et al, , 2023Lee & Shin, 2012), and highlight personal stories (Arbour & McGowen, 2017;Lee & Oh, 2013;McGregor, 2018). The wide-ranging content broadcast by candidates and campaigns reflects their sensitivity to the varied types of information voters seek (Lipsitz et al, 2005).…”
Section: Theory and Previous Researchmentioning
confidence: 99%
“…A further implication is that we have no reason to expect variation based on ideological extremity per se, as it is ideological predilection rather than placement that we expect to matter. This is the crux of the asymmetry versus symmetry accounts -the former, as explained, predict differential response based on policy topics and toxicity while a version of the latter would suggest similar ideological responses but with extremists on both sides generating more variation, potentially being more toxic (e.g., (Schraufnagel et al 2021;Ballard et al 2022). Understanding whether there is ideological asymmetry in retweeting behaviors has substantial implications for isolating the information environments to which those with different ideologies are exposed.…”
mentioning
confidence: 99%